THE EFFECT OF VARIATIONS IN PVC FOAM CORE THICKNESS ON THE FAILURE ANALYSIS OF BENDING TEST IN SANDWICH COMPOSITE - Rodian, Afiko; Paundra, Fajar; Afisna, Lathifa Putri; Nurullah, Fajar Perdana; Pujiyulianto, Eko (Media Mesin: Majalah Teknik Mesin, 2025)
The composite sandwich core is one of the parts that act as an additional material. Despite the thinner core, it should produce a stiff, strong, and lightweight composite, and the higher the bending strength value obtained. This study aims to observe and analyze the influence of core thickness on bending strength and obtain elastic modulus as well as analyze the results of sandwich composite fracture after bending testing. The materials used are polyester resin, 240 gsm twill carbon fiber and core PVC foam. Variations in core thickness of 2 mm, 3 mm, 5 mm, 8 mm, and 10 mm. The method used is vacuum bagging. The tests carried out are bending tests using the ASTM C393 standard. The bending strength value of sandwich composite was obtained at a core thickness variation of 2 mm, which was 81.34 MPa, while the lowest bending strength value was found in a core thickness variation of 10 mm, which was 13.08 MPa.